Proceedings of the International Conference "Actual Issues of Mechanical Engineering" (AIME 2018) 2018
DOI: 10.2991/aime-18.2018.45
|View full text |Cite
|
Sign up to set email alerts
|

Technologies and technical devices for annual regulated flooding of a productive strata

Abstract: Different systems of stratal flooding by mineral or fresh water into oil bearing formation are used today to enhance reservoir recovery. At low temperatures, 25 degrees below zero and lower, there is a great possibility of freezing of the well head equipment due to cyclic flooding or separate horizontal flooding, lessening injection capacity of the well, emergency stops in flooding, due to water pipe breakage or power cutting off. Besides the wells, crossover bends from water injection wells to the pipe header… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…The composition of drill cuttings includes previously used drilling fluid with lost technical properties. The main components of drilling fluids are fluids (water, oil and other organic fluids [10,11]) and barium sulfate. To improve the physicochemical composition of the drilling fluid [12], various additives are used: thickeners (e.g., polyacrylates, other organic polymers), emulsifiers (e.g., alkyl sulfonate acrylate and polyethylene oxide) and deflocculants.…”
Section: Resultsmentioning
confidence: 99%
“…The composition of drill cuttings includes previously used drilling fluid with lost technical properties. The main components of drilling fluids are fluids (water, oil and other organic fluids [10,11]) and barium sulfate. To improve the physicochemical composition of the drilling fluid [12], various additives are used: thickeners (e.g., polyacrylates, other organic polymers), emulsifiers (e.g., alkyl sulfonate acrylate and polyethylene oxide) and deflocculants.…”
Section: Resultsmentioning
confidence: 99%
“…For completeness of laboratory experiments, three values of the length of the working body were selected -80, 120, 160 mm. With a fluid flow rate of 15-20 l/s, the most optimal length of the working body is l = 80 mm, since the device creates a frequency range of 700-930 Hz [7,8]. This frequency range is optimal on the basis of laboratory and experimental studies conducted on the stand and described in [9].…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the studies results presented in the works [1][2][3][4][5][6][7][8][9] showed that the efficiency of the process of oil displacement by water is largely determined by the degree and nature of the interaction of producing and injection wells.…”
Section: Introductionmentioning
confidence: 99%